Rear window [videorecording (Blu-Ray)] - Stewart, James, 1908-1997; Grace, Princess of Monaco, 1929-1982; Corey, Wendell, 1914-1968; Ritter, Thelma; Burr, Raymond, 1917-1993 (2014)
A wheelchair bound photographer spies on his neighbours from his apartment window and becomes convinced one of them has committed murder.